Systemowe zarządzanie organizacjami zhierarchizowanymi: System management in hierarchical organizations - Wyrębek, Henryk (Management and Administration Journal, 2021)
Nowadays, more and more emphasis is placed on improving the quality of customer service in public organizations. Changes in the still integrating European market also force hierarchical organizations to adapt to the new conditions. System management in hierarchical organizations through the development and implementation of formalized management systems can help to increase their effectiveness and efficiency. In practice, in the management of organizations with hierarchical structures more and more attempts to implement systems such as: quality management, environmental management, occupational health and safety and information security management can be seen. The article attempts to assess the functioning of the quality management system in the Department of X Customs Office. For the attainment of the purpose of the article a method of diagnostic survey using questionnaires and interview techniques was used.